Loculoascomycetes of the Botanical garden of Kherson State University (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
The list of the loculoascomycetes of the Botanical garden of Kherson State University is presented. The 28 species 20 genera 13 families 3 orders from class Dothideomycetes were founded. Taxonomical structure, ecological and throphic features of the fungi are considered.
Keywords: loculoascomycetes, diversity, Botanical garden, Kherson.